Directive Speech Acts in The Movie “The Message” By Moustapha Akkad - Asmi Yuniati; Sayyidatul Fadhillah; Muhammad Nafi Annury (Universitas Islam Negeri Walisongo Semarang, 2018)
This study is aimed to explain the classifications and to explain the contribution of directive speech acts analysis in the